2015
DOI: 10.1044/2015_ajslp-14-0017
|View full text |Cite
|
Sign up to set email alerts
|

Telepractice Versus In-Person Delivery of Voice Therapy for Primary Muscle Tension Dysphonia

Abstract: Purpose: The purpose of this study was to investigate the utility of telepractice for delivering flow phonation exercises to persons with primary muscle tension dysphonia (MTD). Method: Fourteen participants with a diagnosis of primary MTD participated, 7 on site and 7 at remote locations. Each participant received 12 treatment sessions across 6 weeks. Treatment consisted of flow phonation voice therapy exercises. Auditory-perceptual, acoustic, aerodynamic, and quality-of-life measures were taken before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
36

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 42 publications
1
29
1
36
Order By: Relevance
“…The voice therapy included five aspects: a. programme on vocal hygiene, b. symptomatic voice therapy (circumlaryngeal massage, chewing exercises, yawn sigh approach, phonation on inhalation), c. Respiratory retraining (Breath support, confidential voice therapy), d. physiologic voice therapy (vocal function exercises, accent method, resonant voice therapy, e. Psychogenic voice therapy. Another study by Rangarathnam et al [24] evaluated the effects of 10-15 minutes of vocal hygiene programme and 20-25 minutes of airflow exercises through tele-therapy mode in individuals with MTD. Positive effects were found in the perceptual and voice related quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The voice therapy included five aspects: a. programme on vocal hygiene, b. symptomatic voice therapy (circumlaryngeal massage, chewing exercises, yawn sigh approach, phonation on inhalation), c. Respiratory retraining (Breath support, confidential voice therapy), d. physiologic voice therapy (vocal function exercises, accent method, resonant voice therapy, e. Psychogenic voice therapy. Another study by Rangarathnam et al [24] evaluated the effects of 10-15 minutes of vocal hygiene programme and 20-25 minutes of airflow exercises through tele-therapy mode in individuals with MTD. Positive effects were found in the perceptual and voice related quality-of-life outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Three additional treatment studies for voice disorders are found in the literature that are not tied to patients with PD (Fu, Theodoros, & Ward, 2015; Mashima et al, 2003; Rangarathnam et al, 2015). Fu et al (2015) delivered intensive voice therapy (i.e., eight sessions over three weeks) via videoconferencing to 10 women with vocal nodules and found significant improvements in acoustic, perceptual, quality-of-life measures, and nodule size at post-treatment, mirroring the outcomes in a separate in-person study.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the efficacy of voice techniques using plastic straw (3) , resonance tube (4,5) and silicon tube (6) has been shown. Electronic technology has also proven useful for voice speech therapy through visual feedback with acoustic analysis software (7) , videos with correct models of voice techniques on portable MP4 players (8) , video games as aids for voice techniques (9) , neuromuscular electrical stimulation (10) and therapy via teleconferencing (11) . Another fast growing area is mobile technology applied to health.…”
Section: Introductionmentioning
confidence: 99%